A Synaptic Function Approach to Investigating Complex Psychiatric Diseases. (June 2014) - Earls, Laurie R.; Zakharenko, Stanislav S.
The 22q11 deletion syndrome (22q11DS) is the most common microdeletion syndrome in humans and presents with a complex and variable psychiatric phenotype. Patients show cognitive impairment and have a higher probability of psychiatric disorders. As much as 30% of patients with 22q11DS suffer from schizophrenia, the strongest association between any mutation and the disease. Schizophrenia is a complex psychiatric disease that affects multiple brain regions, giving rise to a constellation of seemingly unrelated symptoms including hallucinations, social withdrawal, and memory deficits. Synaptic or neuronal malfunctions within certain physiological circuits appear to be at the core of these symptoms. Understanding disease at the synaptic level requires genetic model systems where intact neural circuits can be interrogated for functional deficits. Because of the overlap between 22q11DS and schizophrenia, models of 22q11DS may be key genetic tools for investigating both diseases. Here we discuss the advantages of using a synaptic function approach to studying mouse models of 22q11DS, review recent findings, and discuss them in the broader context of 22q11DS and schizophrenia.